Ocular Manifestations in Children with Special Needs Presenting in a Tertiary Eye Hospital of Central Nepal - Shrestha, Manisha; Kayastha, Sajani; Karki, Rachhaya; Subedi, Kumudini (Journal of College of Medical Sciences-Nepal, 2024)
Background Children with special needs are at a substantially higher risk of visual impairment (VI) (10.5% compared with 0.16%) but also of ocular disorders of all types, including refractive errors and strabismus. VI and other potentially correctable ocular disorders are frequently unidentified in children with complex needs. Although assessment may be more challenging, identifying these potential additional barriers to learning and development may be critical. Methods Detailed ophthalmic examination was carried out in all children with special needs presenting to the Pediatric OPD of Bharatpur Eye Hospital over 6 months (January to June 2023). Ophthalmic examination included case history, presenting distance visual acuity, cycloplegic refraction, binocular vision examination, anterior and posterior segment evaluation. Results Out of the total of 55 participants, mean age was 9.74 ± 5.07 years, majority were male 32 (58.18%). Quantitative visual acuity could be assessed only in 19 (34.55%) children, using picture chart 9 (16.36%) and Snellen chart 10 (18.18%). Strabismus 21 (38.18%) and refractive error 14 (25.45%) were the commonest visual disorders in our study children. Conclusions With patience, suitably adapted methods, visual assessment is feasible in the majority of children with special needs. It is hoped that the formulation of proper vision care guidelines at a national level may help in early detection and management of visual disorders in this special population and enhance their quality of life.